FORMATIVE HISTORY OF THE NOVEL - Atamurodova Feruza Tashmurotovna (Bright Mind Publishing, 2026)
This article delves into the intricate evolution of the novel, tracing its origins from ancient oral traditions to its contemporary forms in today's literary landscape. Through meticulous research and insightful analysis, the author navigates through key historical periods and pivotal moments, illuminating the influences that have shaped the development of the novel as a literary form.
Keywords: Novel, history, genre, period, development, research, literary form, origin.